Culture, immigration and tax compliance - Antoine Malézieux; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
Although understanding how multiculturalism shapes society is imperative in today's globalized world, insights on certain behavior domains remain limited, including those on tax compliance among domestic versus foreign taxpayers. Our meta-study of laboratory tax experiments analyzes over 50,000 tax declaration decisions by almost 5,000 subjects entailing 95 nationalities. Not only do immigrant participants exhibit significantly less tax compliance than natives even with controls for numerous covariates, but tax compliance correlates positively with tax morale, which in turn also interacts significantly with immigration status. Few variables-mainly linked to politics-influenced the gap of compliance between natives and immigrants.
Keywords: C9; H0; H3; 330; Tax evasion; Immigration; Meta-analysis